Her2/neu expression in breast cancer patients - Correlation with estrogen and progesterone receptor status, p53 and Ki-67 immunoreactivity and clinicopathological parameters - Yashar, Genghis; Basheska, Neli; Prodanova, Irina; Vasev, Nikola; Kraleva, Slavica; Ivkovski, Ljube; Kubelka, Katerina; Smichkoska, Snezhana; Zografski, George (Institute of Oncology, Sremska Kamenica, Yugoslavia, 2002)
Although the role of HER2/neu status is still unsettled, its determination is valuable in selecting breast carcinoma patients for adequate Herceptin¨ therapy. The purpose of this study was to investigate the association between HER2/neu expression with estrogen (ER) and progesterone (PgR) receptor status, p53 and Ki-67 immunoreactivity, as well as with other clinicopathological parameters in breast cancer patients. HER2/neu, ER/PgR status, p53 and Ki-67 expression was determined in 169 postoperative stage I-III (UICC, 1997) breast cancer patients using the standardized DAKO HercepsTest¨ and by the immunoperoxidase technique, respectively. The results were evaluated by performing the standardized scoring system. The values of HER2/neu expression were correlated to ER/PgR status, p53 and Ki-67 immunoreactivity and to clinicopathological parameters (tumor size, histopathologic grade, nuclear grade, tumor type, and lymph node status and patients’ age). The statistical significance was determined with c2 and Fisher’s exact test. HER2/neu expression was positive in 66 patients (37%). There was no significant association between the values of HER2/neu and ER/PgR status, p53 or Ki-67 immunoreactivity, neither with any other clinicopathological parameter. ER is associated with PgR, tumor size, tumor type and lymph node status (p<0.01); PgR with histopathologic grade, tumor type and lymph node status (p<0.01) and Ki-67 with p53 immunoreactivity, tumor size and patients’ age (p<0.01). The results of the current study indicate that HER2/neu is an independent prognostic marker in differentiating a subgroup of high-risk breast cancer patients. Additional studies are required to adjust HER2/neu testing results to the clinical outcome.
Keywords: breast neoplasms; HER-2/neu; immunohistochemistry